2013
DOI: 10.1007/s00531-013-0873-9
|View full text |Cite
|
Sign up to set email alerts
|

The geometry of the active strike-slip El Tigre Fault, Precordillera of San Juan, Central–Western Argentina: integrating resistivity surveys with structural and geomorphological data

Abstract: The geometry and related geomorphological features of the right-lateral strike-slip El Tigre Fault, one of the main morphostructural discontinuities in the Central-Western Precordillera of Argentina, were investigated. Achievements of this survey include: recognition of structural and geometrical discontinuities along the fault trace, identification and classification of landforms associated with local transpressional and transtensional sectors, observation of significant changes in the fault strike and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 36 publications
1
29
0
2
Order By: Relevance
“…The eastern flank of the Precordillera, between 31° and 34° S, concentrates most of this active deformation (Costa et al 2006); however, evidence of neotectonic activity has also been reported at the western margin (Cortés and Cegarra 2004;Cortés et al 2005aCortés et al , b, c, 2006Basile 2004;Vallejo 2004;Yamin 2007;Terrizzano 2010). One major example is provided by the El Tigre Fault (Bastías and Bastías 1987;Siame et al 1997bSiame et al , 2006Cortés et al 1999;Fazzito et al 2013).…”
Section: General Geologic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The eastern flank of the Precordillera, between 31° and 34° S, concentrates most of this active deformation (Costa et al 2006); however, evidence of neotectonic activity has also been reported at the western margin (Cortés and Cegarra 2004;Cortés et al 2005aCortés et al , b, c, 2006Basile 2004;Vallejo 2004;Yamin 2007;Terrizzano 2010). One major example is provided by the El Tigre Fault (Bastías and Bastías 1987;Siame et al 1997bSiame et al , 2006Cortés et al 1999;Fazzito et al 2013).…”
Section: General Geologic Settingmentioning
confidence: 99%
“…In the vicinity of the El Tigre Fault zone (Fig. 1a), the Lomas del Campanario Formation is exposed around the Quebrada Ancha area, between 30°47′40″S and 30°49′9″S (~69°13′11″W) (Fazzito et al 2013). The contact between these two formations has not been detected in the field (Bello Camilletti 2012).…”
Section: Stratigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…The upgrading of electric imaging techniques have been widely applied in near-surface geophysics thus contributing to solve geological issues related to active tectonics and fault-trenching analyses (Silva et al, 2001;Caputo et al, 2003;Niviere et al, 2008;Berge, 2014). The combination of new acquisition techniques (multielectrode array configurations) and innovative inversion methods (Loke and Barker, 1996;Patella, 1997) allows the extraction of real-time tomographic images of the subsurface resistivity pattern with high spatial resolution (Griffiths and Barker, 1993).They have been valuable for estimating the fault offset and for locating suitable sites to perform scientific faulttrenches as illustrated in several studies (Niviere et al, 2008;Grützner et al, 2012, Stephanickova et al, 2013Fazzito et al, 2013;Karabacak et al, 2013;Berge, 2014).…”
Section: A) Geophysicsmentioning
confidence: 99%
“…En general son fallas inversas, que inclinan en algunas secciones al este y en otras al oeste, casi siempre con ángulos elevados. Por otro lado, se puede mencionar el Sistema de Fallas El Tigre ubicado en el piedemonte occidental de Precordillera Occidental, definido por Bastías (1985) y descripto por Siame et al (1997Siame et al ( , 2006, Costa (2000) y Fazzito et al (2013), entre otros autores.…”
Section: Introductionunclassified